Tri-level hybrid interval-stochastic optimal scheduling for flexible residential loads under GAN-assisted multiple uncertainties - Wang, Xiaofei; Li, Fangxing; Zhao, Jin; Olama, Mohammed; Dong, Jin; Shuai, Hang; Kuruganti, Teja (International journal of electrical power & energy systems, 2023)
•A tri-level distribution market framework considering uncertainties is proposed.•A hybrid interval-stochastic model transforms uncertain problems to deterministic.•Generative Adversarial Networks (GANs) creates uncertain PV solar scenarios.•A rolling horizon optimization scheme is employed for continuous optimization.•Case studies validate the effectiveness of the proposed algorithm. Various building loads, such as heating, ventilation, and air conditioners (HVACs), electric water heaters (EWHs), and electric vehicles (EVs), can introduce opportunities for improving the flexibility of electricity consumption while satisfying the needs of building owners as well as benefiting the resilience of distribution system. To utilize such flexibility, a tri-level distribution market framework is established, including residential consumers, load aggregators (LAs), and the distribution system operator (DSO). The uncertainties from all three levels are considered. The random consumption behavior at the consumer level is modeled as a Gaussian noise that is also aggregated and transmitted to the LA level. The weather temperature in the LA level is forecasted as an interval, and the photovoltaic (PV) power in the market-clearing level is modeled by a set of power scenarios generated by Generative Adversarial Networks (GANs). Then, a hybrid interval-stochastic programming is proposed to transform the uncertain problems in the first two levels into deterministic ones. For real-time implementations, a rolling horizon optimization (RHO) scheme is employed to continuously optimize the power consumption based on the latest operating information. Finally, case studies on a modified IEEE 69-bus system validate the effectiveness of the proposed uncertainty modeling strategies and the RHO scheme.